Electronic Structure, Electric Moments and Vibrational Analysis of 3-(2-Methoxyphenoxy) Propane-1,2-Diol by Ab Initio and Density Functional Theory (Journal of Atomic and Molecular Sciences, 2011)
The molecular properties and harmonic wavenumbers of 3-(2-methoxyphenoxy) propane-1,2-diol have been calculated using ab initio and density functional theory. The polarizability and first static hyperpolarizability of the title molecule have been calculated at different basis sets. In general a good agreement between experimental and calculated normal modes has been observed. The frontier orbital and molecular electrostatic potential surface study has also been employed to understand the active sites of 3-(2-methoxyphenoxy) propane-1,2-diol.